The Roles of Organizational Commitments in Mediating The Effects of Work Motivation and Satisfaction on Employee Performance of Siesta Legian Hotel - Ni Luh Yeni Pusparini (JUSTBEST: Journal of Sustainable Business and Management, 2021)
This study aims to determine the Role of Organizational Commitments in Mediating the Effects of Work Motivation and Satisfaction on Employee Performance at Siesta Legian Hotel.The sample in this study includes male and female employees of all departments at Siesta Legian Hotel. The method of determining the sample in this study uses a non-probability sampling method with a saturated sample method or with a census technique term where the numbers of the samples in this study were 72 people. The examination of the hypothesis research uses Partial Least Square (PLS) applications. The results of the study indicate that:(1) Motivation has a negative and not significant influence against the employee performance. (2) Job satisfaction has positive and significant influences against the employee performance. (3) Motivation has positive influences, but it is not significant against the organizational commitment. (4) Job satisfaction has positive and significant influences against the organizational commitment. (5) Organizational commitment has positive and significant influences against the employee performance. (6) Organizational commitment is not able to mediate the influence of motivation against the employee performance. (7) Organizational commitment mediates part of the influence of job satisfaction against the employee performance.